Female Fertility Has a Negative Relationship With Longevity in Chinese Oldest-Old Population: A Cross-Sectional Study - Zhu, Qiao; Fu, Shihui; Zhang, Qian; Tian, Jinwen; Zhao, Yali; Yao, Yao (Frontiers in Endocrinology, 2021)
Background: Despite research efforts in this field for more than a century, the relationship between female fertility and longevity is unclear. This study was designed to investigate this relationship in Chinese oldest-old population. Methods: The China Hainan Centenarian Cohort Study was performed in 18 cities and counties of Hainan. A total of 1226 females, including 758 centenarian women and 468 women aged 80–99 years, were enrolled in this study. Using a standardized protocol, in-person interviews and blood analyses were conducted by a well-trained research team through home visits. Results: Centenarian women had significantly lower number of children (NOC) and higher initial childbearing age (ICA) and last childbearing age (LCA) than women aged 80–99 years (p < 0.05 for all). Multivariate logistic regression analysis showed that NOC and testosterone (T) levels were positively associated with women aged 80–99 years, when centenarian women was considered as reference (p < 0.05 for all). ICA, LCA and estradiol (E2) levels were negatively associated with women aged 80–99 years, when centenarian women was considered as reference (p < 0.05 for all). Conclusions: The centenarians had crucial characteristics of less and delayed childbearing, indicating a negative relationship between female fertility and longevity in Chinese oldest-old population. Serum E2 levels were positively associated and serum T levels were negatively associated with longevity. The less and late childbearing might be a significant factor of longevity, and successful aging might be promoted by reducing and delaying female childbearing.